2006
DOI: 10.1186/1471-2458-6-263
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the evaluation of outbreak detection methods

Abstract: Background: An increasing number of methods are being developed for the early detection of infectious disease outbreaks which could be naturally occurring or as a result of bioterrorism; however, no standardised framework for examining the usefulness of various outbreak detection methods exists. To promote comparability between studies, it is essential that standardised methods are developed for the evaluation of outbreak detection methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…This approach has been documented in a number of previous studies, which have compared the performance of early outbreak detection algorithms using simulated outbreaks [11][12][13][14][15][16][17][18]. The simulation enables the performance assessment and provides much-need comparative findings about outbreak detection algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been documented in a number of previous studies, which have compared the performance of early outbreak detection algorithms using simulated outbreaks [11][12][13][14][15][16][17][18]. The simulation enables the performance assessment and provides much-need comparative findings about outbreak detection algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…By reviewing the recently published literature for reports that evaluated methods for the detection of infectious disease outbreaks in public health surveillance data, Watkins et al . categorized evaluation methods into four main methods: the descriptive, derived, epidemiological and simulation approaches, and concluded that no single approach could fulfill all evaluation requirements [41]. So, the appropriate model should be selected through comprehensive consideration and conscientious analysis according to the actual circumstance, and be promptly adjusted in relation to specific conditions in the community, changes in the pattern of life and the natural history of disease.…”
Section: Discussionmentioning
confidence: 99%
“…For this, we need datasets with clearly identified and delimited (in time) health events. While such data may be more easily available or derived for large well-defined seasonal outbreaks, the use of a small number of variables to define the occurrence of an outbreak may constitute a limited indicator and result in smaller outbreaks being missed [99]. Alternatively, expert judgement may be used retrospectively to determine the occurrence of events of public health importance, often using resource-intensive epidemiological investigation techniques.…”
Section: Discussionmentioning
confidence: 99%